Treatment of the inflamed dental pulp - De Souza, V.; Holland, R. (Wiley, 1974)
Abstract— Anterior teeth of dogs, whose pulps were experimentally exposed to oral environment for 48 hours had their crowns removed for histopathological examination of the pulpal tissue. The radicular pulps were capped with antibiotic, corticosteroid and calcium hydroxide; these drugs were utilized alone or in combinations. After 90 days, histological examination of the pulps demonstrated the value of calcium hydroxide. 1974 Australian Dental Association